Challenges of Pair Work Activity in EFL Writing Classroom: A Narrative Review - Aprillia, Olvi; Zur, Sarjaniah; Atikah, Dewi; Wahyuddin Masdin, M (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This narrative review aims to identify the challenges of pair-work activities in EFL writing classrooms based on a comprehensive analysis of recent research. The data in this study were drawn from 20 articles published between 2013 and 2023. The results of the data analysis revealed four main challenges in implementing pair work for EFL writing: unequal participation, conflicting ideas and negotiation, differences in task progress and completion, and differences in language proficiency and language-related issues. This inquiry found that unequal participation and language proficiency disparities were the most frequently reported challenges across the studies. This study could specifically increase teachers' awareness of the potential obstacles in collaborative writing especially in pair work activities and help them develop strategies to mitigate these challenges, as it is hoped that addressing these issues will lead to more effective pair work implementation and improved learning outcomes in EFL writing classrooms.